Optimal conditions for CASA-Mot analysis of boar semen: Effect of frame rate for different chambers and sperm count fields - Barquero, Vinicio (2021)
The aim of the study was to determine the effect of the frame rate on different depths of the sperm counting chamber in boar semen and to analyse the distribution of sperm in the longitudinal fields of the counting chamber. A semen sample was collected from ten 2–3-year-old Pietrain boars. Eight sperm kinetic parameters were determined using the CASA (Computer-assisted semen analysis) -Mot (ISAS®v1) system. ISAS®D4C cameras with depths of 10, 16 and 20 μm were used at an image capture rate of 25, 40 and 60 frames per second (fps). Chamber depth affected the sperm kinetic variables, obtaining higher values at 20 µm. The frame rate (FR) presented a positive relationship with the kinetic parameters, obtaining higher values at 60 fps, except for the amplitude of the lateral displacement of the head (ALH), which presented opposite values. The variable most sensitive to the change in FR was the curvilinear velocity (VCL), where the best level was observed with 80 fps. A progressive decrease in kinematic patterns was observed as sperm advanced through the fields of the chambers. It is concluded that the use of different counting chambers and the increase in the total number of fps generates significant changes in the estimation of sperm kinetics parameters in the boar.